Healthy lifestyles in relation to cardiometabolic diseases among schoolteachers: A cross‐sectional study - Liyan Huang; Mengjie He; Jie Shen; Yiying Gong; Hui Chen; Xiaolin Xu; Geng Zong; Yan Zheng; Chao Jiang; Baohong Wang; Ronghua Zhang; Changzheng Yuan (Wiley, 2023)
Abstract Background We aimed to explore the associations of adherence to an overall healthy lifestyle with cardiometabolic diseases (CMDs) among schoolteachers in China. Methods We conducted a cross‐sectional analysis among 2983 teachers (aged 39.8 ± 9.3 years, 73.8% women) in Zhejiang Province, China. A healthy lifestyle score (0-7) was constructed based on seven low‐risk factors: healthy diet, noncurrent smoking, noncurrent drinking, regular exercise, normal body mass index (BMI), adequate sleep duration, and limited sedentary behavior. CMDs included self‐reported hyperlipidemia, hypertension, diabetes, coronary heart disease, and stroke. Multivariable‐adjusted logistic regression models were used to evaluate the associations between healthy lifestyle and CMD. Results A total of 493 (16.5%) participants had at least one CMD, with hyperlipidemia, hypertension, and diabetes being the three leading CMDs. Each point increment in a healthy lifestyle score was associated with 20% lower odds of having CMD (p‐trend < 0.001). Compared with 0-3 low‐risk factors, the odds ratios (ORs) and 95% confidence intervals (CIs) were 0.66 (0.50-0.88) for 4 low‐risk factors and 0.51 (0.39-0.67) for 5-7 low‐risk factors. We observed independent associations for normal BMI (OR = 0.50, 95% CI = 0.40-0.63), noncurrent drinking (OR = 0.53, 95% CI = 0.36-0.77), and limited sedentary behavior (OR = 0.77, 95% CI = 0.62-0.96) in relation to CMD. Healthy diet (OR = 0.75, 95% CI = 0.55-1.01) exhibited marginally significant association with CMD. Conclusions Our findings suggest that adherence to an overall healthy lifestyle is associated with lower odds of CMD among schoolteachers.